Predicting Impulsive Buying Influenced by Hedonic Motivation and Socialization Motivation - Sugiono, Burhan Prakoso; Yuliana, Lingga; Larasati, Nike; Febrian, Wenny Desty (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2025)
The purpose of this study is to determine how socialization and hedonic motivation affect impulsive purchasing. The sampling method is called purposeful sampling. One hundred respondents, ages twelve to fourteen, participated in the survey. Partial Least Squares is one of the data analysis techniques used in this study's quantitative approach. As a data analysis tool, SmartPLS version 4 is used to process data. Primary data from Google Forms used to distribute questionnaires is used in the data source. The study's findings suggest that impulsive purchasing is influenced by hedonic motivation. The second hypothesis, however, demonstrates that impulsive purchasing is unaffected by socialization motivation. According to the management implications of this study, businesses who provide goods and services to teenagers should think about the advantages, quality, and selling price. Teenagers are a tech-savvy generation, thus all decisions are based on user feedback and considerations. If the selling price is too expensive for the teenagers, they will abandon their plan to purchase